PELATIHAN METODE PEMBELAJARAN BAHASA INGGRIS MELALUI FREE VIRTUAL ONLINE COURSE - Ayu dan Nurhayati2 Bandu Retnomurti1 (Faktor Jurnal Ilmiah Kependidikan, 2015)
Abstract: The specific purpose of implementation in practicing is to identify the English learning autonomously by virtual online course, especially for students in LPK NUANSA JAYA Kota Bambu Selatan Palmerah Jakarta Barat. The output product is giving the innovation of English method for students such as the model of English learning by free virtual online course which shows the example of e-learning appllication. So, the result of this practicing can increase the ability of students in browsing English website autonomously. This model is more effective, in addition the facility of free online English course website is larger to browse. The implementation of this activity by three techniques or methods such as accelerated, purpose-based, and cooperative method. The implementation result of free virtual online course methods are the first is (1) accelerated method is the method which make students faster in English learning process by three stages like getting material, doing exercise, and evaluation. (2) The second method is purpose-based method which focuses is how to use free online English course by adapting the types of ability which want to increase it. Whereas, (3) the third method is cooperative method which focuses is how to use the facilities in free online English course by classifying website that provide the facilities such as chat rooms, chat groups, and English forum. Keywords: English learning autonomously; Free Virtual Online Course; Accelerated; Purpose-based; and Cooperative methods.